Constructive Deviance in Organizations: Integrating and Moving Forward - Abhijeet K. VADERA (Institutional Knowledge at Singapore Management University, 2013)
A growing literature explores the notion of constructive deviance conceptualized as behaviors that depart from the norms of the reference group such that they benefit the reference group and conform to hypernorms. We argue that constructive deviance is an umbrella term that encompasses several different behaviors, including taking charge, creative performance, expressing voice, whistle-blowing, extra-role behaviors, prosocial behaviors, prosocial rule breaking, counter-role behaviors, and issue selling. Using the three common mechanisms underlying constructive deviance to organize our review (intrinsic motivation, felt obligation, and psychological empowerment), we provide an emergent model that integrates extant empirical work on the antecedents of constructive deviance. We conclude by discussing issues for future research, such as examining obstacles, outcomes, and unexplored mechanism dynamics associated with constructive deviance.